From Moral Annihilation to Luciferism: Aspects of a Phenomenology of Violence - James G. Hart (Eidos. A Journal for Philosophy of Culture, 2017)
Do the various ascriptions of “violence,” e.g., to rape, logical reasoning, racist legislation, unqualified statements, institutions of class and/or gender inequity, etc., mean something identically the same, something analogous, or equivocal and context-bound? This paper argues for both an analogous sense as well as an exemplary essence and finds support in Aristotle’s theory of anger as, as Sokolowski has put it, a form of moral annihilation, culminating in a level of rage that crosses a threshold. Here we adopt Sartre’s analysis of the “threshold of violence” as indicating a basic “existential” possibility wherein persons may and do adopt a posture of anti-god. This has considerable symmetry with the mythic and theological figure in the Abrahamic religions who is called “Lucifer.” This personage, at a unique timeless moment, found himself empowered to assume the right to exercise an infinite will-act which tolerated no superior normative perspective. I argue that this mythic stance is a live option for persons. Further, modern day nation-state military preparedness, where nuclear weaponry is a major tool of foreign policy, is a way of putting on ice and holding in reserve, but button ready, the onto-logical madness of the Luciferian moment.